2019
DOI: 10.1002/jlb.4mr0119-035r
|View full text |Cite
|
Sign up to set email alerts
|

Fat, fight, and beyond: The multiple roles of lipid droplets in infections and inflammation

Abstract: Increased accumulation of cytoplasmic lipid droplets (LDs) in host nonadipose cells is commonly observed in response to numerous infectious diseases, including bacterial, parasite, and fungal infections. LDs are lipid‐enriched, dynamic organelles composed of a core of neutral lipids surrounded by a monolayer of phospholipids associated with a diverse array of proteins that are cell and stimulus regulated. Far beyond being simply a deposit of neutral lipids, LDs have come to be seen as an essential platform for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 202 publications
(678 reference statements)
5
59
0
2
Order By: Relevance
“…Blockage of DGAT-1 activity lead to inhibition of the LDs and significantly reduced leukotriene production and cytokine released by monocytes, suggesting an important role for LDs to control the inflammatory process, and consequently to prevent the cell death-related with the uncontrolled inflammatory process. This finding is in agreement with the well-established role of LDs in inflammation and innate immunity (Bozza and Viola, 2010;Pereira-Dutra et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Blockage of DGAT-1 activity lead to inhibition of the LDs and significantly reduced leukotriene production and cytokine released by monocytes, suggesting an important role for LDs to control the inflammatory process, and consequently to prevent the cell death-related with the uncontrolled inflammatory process. This finding is in agreement with the well-established role of LDs in inflammation and innate immunity (Bozza and Viola, 2010;Pereira-Dutra et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Most positive-strand RNA virus are able to modulate the host lipid metabolism and to highjack LDs to enhance their fitness and replication/particle assembling capacity (Herker and Ott, 2012;Pereira-Dutra et al, 2019). The pathways and mechanisms used may vary according to the virus and the host cell infected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered only as lipid storage for a long time, their functions are increasingly being expanded. Currently, they are deemed central hubs of the lipid homeostasis, also involved in virus infection and the immune responses ( Heaton and Randall, 2011 ; Saka and Valdivia, 2012 ; Zhang et al, 2017 ; Pereira-Dutra et al, 2019 ). In fact, LD formation is a frequently observed event occurring in cells from the immune system during viral infection ( Saka and Valdivia, 2012 ; Pereira-Dutra et al, 2019 ).…”
Section: Lipid Droplets Involvement In (+)Ssrna Virus Infectionmentioning
confidence: 99%
“…When needed, lipids are mobilized and hydrolyzed by specific lipases, such as adipose triglyceride lipase, to yield intermediary metabolites (such as DAGs, FFAs, phosphatidic acid, and sterols) necessary for the membrane synthesis, energy production through β-oxidation, and other anabolic reactions ( Walther and Farese, 2012 ; Pol et al, 2014 ; Zhang et al, 2017 ). Cholesterol and FA depletion influences LD size and surface, which is a binding site of different proteins and enzymes, some of them involved in lipid synthesis and mobilization, such as DGAT2, cPLA2α, and other lipases ( Yu et al, 1998 ; Kuerschner et al, 2008 ; Tirinato et al, 2017 ; Pereira-Dutra et al, 2019 ). Recent works have also suggested that HMGCR degradation, which generally occurs in response to high cholesterol levels, takes place on the LD surface ( Hartman et al, 2010 ).…”
Section: Lipid Droplets Involvement In (+)Ssrna Virus Infectionmentioning
confidence: 99%